Philo of Alexandria: An Annotated Bibliography 1997-2006 - Runia, David T. (Vigiliae Christianae, Supplements. Texts and Studies of Early Christian Life and Language, 2012)
This volume is a further continuation of the annotated bibliographies on the writings and thought of the Jewish exegete and philosopher Philo of Alexandria prepared by Roberto Radice and David Runia for the years 1937–1986 published in 1988 and by David Runia for the years 1987–1996 published in 2000. Prepared with the collaboration of the International Philo Bibliography Project, it contains a complete listing of all scholarly writings on Philo for the period 1997 to 2006. Part One lists texts, translations, commentaries etc. (58 items). Part Two contains critical studies (1024 items). In part Three additional works for the years 1987–1996 are presented (42 items). In all cases a brief description of the contents of the contribution is given. Seven indices, including a detailed Index of subjects, complete the work